Beasts, Savages, and Beyond: Review of Michael Lundblad, The Birth of a Jungle: Animality in Progressive-Era U.S. Literature and Culture - Koncul, Ana (Humanimalia, 2014)
Michael Lundblad, The Birth of a Jungle: Animality in Progressive-Era U.S. Literature and Culture. Oxford: Oxford UP, 2013. 240 pp. 65.00.